Case series analysis of hindfoot injuries sustained by drivers in frontal motor vehicle crashes. (September 2015) - Ye, Xin; Funk, James; Forbes, Aaron; Hurwitz, Shepard; Shaw, Greg; Crandall, Jeff; Freeth, Rob; Michetti, Chris; Rudd, Rodney; Scarboro, Mark
Highlights: 34 cases with leg, foot, and ankle injuries from CIREN database were queried and analyzed. Axial loading was the predominant loading mechanism for hind-foot injuries. Efforts to reduce hind-foot injuries should be prioritized in crash prevention. Abstract: Improvements to vehicle frontal crashworthiness have led to reductions in toe pan and instrument panel intrusions as well as leg, foot, and ankle loadings in standardized crash tests. Current field data, however, suggests the proportion of foot and ankle injuries sustained by drivers in frontal crashes has not decreased over the past two decades. To explain the inconsistency between crash tests results and real world lower limb injury prevalence, this study investigated the injury causation scenario for the specific hind-foot injury patterns observed in frontal vehicle crashes. Thirty-four cases with leg, foot, and ankle injuries were selected from the Crash Injury Research and Engineering Network (CIREN) database. Talus fractures were present in 20 cases, representing the most frequent hind-foot skeletal injuries observed among the reviewed cases. While axial compression was the predominant loading mechanism causing 18 injuries, 11 injured ankles involved inversion or eversion motion, and 5 involved dorsiflexion as the injury mechanism. Injured ankles of drivers were more biased towards the right aspect with foot pedals contributing to injuries in 13 of the 34 cases. Combined, the results suggest that despite recent advancement of vehicle performance in crash tests, efforts to reduce axial forces sustained in lower extremity should be prioritized. The analysis of injury mechanisms in this study could aid in crash reconstructions and the development of safety systems for vehicles.